Cordia verbenacea and secretion of mast cells in different animal species - Costa de Oliveira, Deborah Mara [UNESP]; Luchini, Ana Carolina [UNESP]; Seito, Leonardo Noboru [UNESP]; Gomes, Jose Carlos [UNESP]; Crespo-Lopez, Maria Elena; Di Stasi, Luiz Claudio [UNESP] (Elsevier B.V., 2011)
Ethnopharmacology relevance: Different plant species from Cordia genera are used in folk medicine as anti-inflammatory medication throughout the tropical and subtropical regions of the world. In Brazil, Cordia verbenacea is a medicinal plant known as "erva-baleeira". The alcoholic extracts, decoctions and infusions with leaves of C. verbenacea are used in Brazilian traditional medicine for treatment of cough, pneumonia, parasitic diseases and, especially, the inflammatory processes. Anti-inflammatory activity was already demonstrated; however, molecular mechanisms of action are not completely understood. Considering the importance of histamine in early events of inflammation and in allergic diseases, we evaluated the effect of ethanol extract of leaves of C. verbenacea on histamine release (in vitro and in vivo studies) from different types of mast cells induced by chemical agents using several species of rodents.Materials and Methods: The extraction and quantification of histamine were performed by using an automatic fluorometric continuous flow system.Results: The extract of C. verbenacea (30 mu g/ml) reduced the in vitro secretion of histamine from rat mast cells induced by ionophore A23187, concanavalin A and compound 48/80, respectively, to 22.1 +/- 2.2%, 24.3 +/- 2.5% and 21.4 +/- 2.1%. At the same concentration, the extract also inhibited the secretion of histamine from mast cells of guinea pig induced by ionophore A23187 to 33.3 +/- 2.2%, and mast cells of hamster induced by ionophore A23187 and concanavalin A to 15.8 +/- 2.5% and 10.8 +/- 2.6%, respectively. The oral treatment with the extract (300 mg/kg) also inhibited the secretion of histamine induced by A23187 about to 36.3 +/- 3.2% in rats.Conclusions: C. verbenacea inhibits the in vitro secretion of histamine from mast cells of different animal species, as well as the secretion of mast cells from animals treated with the extract, which gives not only the proven anti-inflammatory effect of the plant, but also anti-allergic effect, opening new possibilities for future anti-allergic herbal medicine. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Boraginaceae; Cordia verbenacea; Mast cell; Histamine; Inflammation; Allergy